NUMERICAL SIMULATION OF POLLUTION DISPERSION IN URBAN STREET - Biliaiev, M. M.; Slavinska, O. S.; Kyrychenko, R. V. (Science and Transport Progress, 2017)
Purpose. The scientific paper solves the question of 2D numerical model development, which allows quick computation of air pollution in streets from vehicles. The aim of the work is numerical model development that would enable to predict the level of air pollution by using protective barriers along the road. Methodology. The developed model is based on the equation of inviscid flow and equation of pollutant transfer. Potential equation is used to compute velocity field of air flow near road in the case of protection barriers application. To solve equation for potential flow implicit difference scheme of «conditional approximation« is used. The implicit change – triangle difference scheme is used to solve equation of convective – diffusive dispersion. Numerical integration is carried out using the rectangular difference grid. Method of porosity technique («markers method») is used to create the form of comprehensive computational region. Emission of toxic gases from vehicle is modeled using Delta function for point source.Findings. Authors developed 2D numerical model. It takes into account the main physical factors affecting the process of dispersion of pollutants in the atmosphere when emissions of vehicle including protection barriers near the road. On the basis of the developed numerical models a computational experiment was performed to estimate the level of air pollution in the street. Originality. A numerical model has been created. It makes it possible to calculate 2D aerodynamics of the wind flow in the presence of noises and the process of mass transfer of toxic gas emissions from the motorway. The model allows taking into account the presence of the car on the road, the form of a protective barrier, the presence of a curb. Calculations have been performed to determine the contamination zone formed at the protective barrier that is located at the motorway. Practical value. An effective numerical model that can be applied in the development of environmental protection measures for the operation of road transport in the city is considered. The developed model allows estimating sizes, the form and intensity of a zone of pollution at a motorway.